2014
DOI: 10.1055/s-0034-1384522
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Sensitivity to Glucagon and Related Peptides in Primary Adrenal Cushing’s Syndrome

Abstract: Illegitimate G-protein coupled receptors are known to control cortisol secretion in adrenal adenomas and bilateral macronodular adrenal hyperplasias (BMAHs) causing Cushing's syndrome. In the present study, we have evaluated the role of glucagon in the regulation of cortisol secretion in 13 patients with BMAH or adrenocortical adenoma causing subclinical or overt Cushing's syndrome. Injection of glucagon provoked an increase in plasma cortisol in 2 patients. After surgery, immunohistochemical studies showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Furthermore, 5-HT 7 receptor agonists were also found to stimulate cortisol production from an adrenal carcinoma that also produced rennin (71). The presence of ectopic glucagon receptors was demonstrated in patients with subclinical or overt CS (47,72,73,74,75). Injection of glucagon increased cortisol in two out of 13 patients with BMAH or unilateral adenoma.…”
Section: European Journal Of Endocrinologymentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, 5-HT 7 receptor agonists were also found to stimulate cortisol production from an adrenal carcinoma that also produced rennin (71). The presence of ectopic glucagon receptors was demonstrated in patients with subclinical or overt CS (47,72,73,74,75). Injection of glucagon increased cortisol in two out of 13 patients with BMAH or unilateral adenoma.…”
Section: European Journal Of Endocrinologymentioning
confidence: 94%
“…Injection of glucagon increased cortisol in two out of 13 patients with BMAH or unilateral adenoma. In vitro studies revealed the presence of glucagon receptor-like immunoreactivity in clusters of spongiocytic cells in adrenal tissues from patients who were sensitive in vivo to glucagons (75). Expression of somatostatin receptors SSTRs (particularly of SSTR1-3) was increased in PPNAD tissues carrying a PRKAR1A mutation compared to normal adrenal and to tissues from other adrenal diseases.…”
Section: European Journal Of Endocrinologymentioning
confidence: 98%
“…Among the 19 cases of corticomedullary mixed tumors reported in the literature, seven patients presented catecholamine overproduction that was associated with hypercortisolism in three cases (57,59,60). In very much the same way, our group has described the occurrence of clusters of chromogranin A-positive chromaffin cells disseminated in adrenocortical adenoma responsible for hyperaldosteronism (61) or subclinical Cushing's syndrome (62).…”
Section: Sources Of Paracrine Regulatory Factors In Adrenocortical Nementioning
confidence: 79%
“…More recently, several groups have reported activating mutations of the gene of the catalytic subunit of PKA (PRKACA) in cortisol-secreting adrenal adenomas; these data are reviewed by Espiard et al [24]. In a specific form of bilateral adrenal tumor (macronodular adrenal hyperplasia) causing cortisol excess, Louiset et al [25] present how abnormal expression of membrane receptors that signal trough cAMP/PKA can be shown. Basso et al [26] show the important role of the regulatory subunits R1A and R2B of PKA in the adrenocortical cell cycle.…”
Section: Pde 2013 Paris France: Another Exciting Workhop For Cyclimentioning
confidence: 99%